1999
DOI: 10.1021/jp9916135
|View full text |Cite
|
Sign up to set email alerts
|

Excited State Properties of Peridinin:  Observation of a Solvent Dependence of the Lowest Excited Singlet State Lifetime and Spectral Behavior Unique among Carotenoids

Abstract: The spectroscopic properties and dynamic behavior of peridinin in several different solvents were studied by steady-state absorption, fluorescence, and transient optical spectroscopy. The lifetime of the lowest excited singlet state of peridinin is found to be strongly dependent on solvent polarity and ranges from 7 ps in the strongly polar solvent trifluoroethanol to 172 ps in the nonpolar solvents cyclohexane and benzene. The lifetimes show no obvious correlation with solvent polarizability, and hydrogen bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
475
1
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(515 citation statements)
references
References 36 publications
36
475
1
3
Order By: Relevance
“…It can be speculated that the cyclopentanone ring is involved in this localization step. This assumption is likely because other groups having observed a decay pattern very similar to the one reported here, made their observations in peridinin, a carotenoid highly substituted and possessing a cyclopentanone ring as well [99][100][101][102]. This assumption is further corroborated by experimental results obtained on magnesium octaethylporphyrin (MgOEP) (data not shown) as MgOEP, in contrast to the structurally similar PChla, which in addition has an attached cyclopentanone ring to the porphyrin macrocycle, does not exhibit any significant excited-state dynamics, when directly being promoted into the Q 00 band [22].…”
Section: Protochlorophyllide Asupporting
confidence: 81%
See 1 more Smart Citation
“…It can be speculated that the cyclopentanone ring is involved in this localization step. This assumption is likely because other groups having observed a decay pattern very similar to the one reported here, made their observations in peridinin, a carotenoid highly substituted and possessing a cyclopentanone ring as well [99][100][101][102]. This assumption is further corroborated by experimental results obtained on magnesium octaethylporphyrin (MgOEP) (data not shown) as MgOEP, in contrast to the structurally similar PChla, which in addition has an attached cyclopentanone ring to the porphyrin macrocycle, does not exhibit any significant excited-state dynamics, when directly being promoted into the Q 00 band [22].…”
Section: Protochlorophyllide Asupporting
confidence: 81%
“…This strikingly different decaying behavior deserves some thorough considerations. The experimental findings discussed so far might be explained on the basis of a split S 1 state in analogy to arguments given by Zigmantas et al [99] and Bautista et al [100] to account for the observed excited-state dynamics of peridinin, a highly substituted carotenoid. The second state involved would most likely possess intramolecular charge-transfer (ICT) character and is therefore stabilized in more polar solvents and -in turn -destabilized in a nonpolar environment.…”
Section: Protochlorophyllide Asupporting
confidence: 64%
“…The broadening and red-shifting of the 39-hECN chromophore in the OCP and RCP, attributed to conformational heterogeneity of 39-hECN in these proteins, as well as orientation and local environment of the carbonyl oxygen, has been discussed in detail elsewhere (Polívka et al, 2005;Chábera et al, 2011;Berera et al, 2012). Similar effects are observed in the absorption spectra for other carotenoids with conjugated carbonyl groups when dissolved in polar solvents (Bautista et al, 1999;Frank et al, 2000). The reduced A 280 in the RCP spectrum is consistent with the loss of aromatic amino acids associated with the C-terminal domain.…”
Section: Spectroscopic Characterization Of Ocp O Ocp R and Rcpmentioning
confidence: 66%
“…Instead of an internal electron withdrawing group (such as a carbonyl), the interaction with polar amino acids, inorganic cations such as Mg 2ϩ or nearby pigments, resulting in a highly asymmetric environment of the molecule, may stabilize an ICT state. Also, geometric deformations of the polyene backbone have been proposed to play a role in lowering ICT states in carotenoids (30). Trimeric LHCII binds two luteins that are distinguishable by their steady-state absorption spectrum.…”
Section: Discussionmentioning
confidence: 99%